Supervisors' Leadership Styles And Subordinates' Performance In Palestinian Public Organizations: The Mediating Role Of Communication Satisfaction - Alsayed, Alaedin K. I. (2012)
The purpose of this study was to examine the effect of each of the three leadership styles of supervisors (transformational, transactional, and laissez-faire) on employees' job performance and leadership outcomes in terms of (extra effort, satisfaction with leader, and leader's effectiveness). The study also examined the mediating effect of employees' communication satisfaction, which is conceptualized as a multidimensional construct consisting of three factors (informational, relational, and informational/relational).